Molecular structure, spectroscopic signature and reactivity analyses of paracetamol hydrochloride monohydrate salt using density functional theory calculations. Issue 5 (3rd January 2019) - Srivastava, Karnica; Shukla, Anuradha; Karthick, T.; Velaga, Sitaram P.; Tandon, Poonam; Sinha, Kirti; Shimpi, Manishkumar R.
Abstract : Spectroscopic and quantum chemical study on paracetamol hydrochloride monohydrate. Abstract : The aim of this study was to understand the role of the intermolecular hydrogen bond interactions present in paracetamol hydrochloride monohydrated salt. Paracetamol hydrochloride monohydrate salt (PRA-HCl) and paracetamol (form I) were investigated via vibrational (FT-IR and FT-Raman) spectroscopy and density functional theory (DFT) to gain insight into the hydrogen bond patterns present in these crystalline materials. Two different density functionals, wB97X-D and M062X, were used for the comparison of the results. The geometrical parameters of PRA-HCl and form I obtained using these functional were compared with the crystallographic data, which proved the existence of intra-molecular and intermolecular hydrogen bonds. The C10O2 group of form I forms an intramolecular hydrogen bond, while the O1–H18 group of PRA-HCl forms an intermolecular hydrogen bond with a chloride ion (Cl − ), resulting in the elongation of the bond length and shift to a lower wavenumber for the O1–H18 group. To examine the potency of hydrogen bonding, quantum theory of atoms in molecules (QTAIM) calculations were performed and the results suggested that O1–H18⋯Cl22 is a strong intermolecular hydrogen bond. The chemical reactivity parameters reveal that the PRA-HCl and PRA-OXA cocrystals are more reactive and softer (low HOMO–LUMO energy gap) in comparison to paracetamol (form I).